2017
DOI: 10.1590/s1806-37562016000000298
|View full text |Cite
|
Sign up to set email alerts
|

Survival in a cohort of patients with lung cancer: the role of age and gender in prognosis

Abstract: Objective:To determine the demographic and clinical characteristics of patients with non-small cell lung cancer (NSCLC), as well as their disease course, by age group and gender. Methods:This was a retrospective cohort study of patients diagnosed with NSCLC from 2000 to 2012 and followed until July 2015 in a tertiary referral hospital in the city of São Paulo, Brazil. Based on the 25th and 75th percentiles of the age distribution, patients were stratified into three age groups: < 55 years; ≥ 55 and < 72 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…As for age, there seem to be controversies in previous studies, with some researchers believing that old age is associated with worse survival 27,28 and others not believing this. 29,30 In our study, we also found that old age was associated with worse survival in only the solid group (p ¼ 0.030) and not in the part-solid group (p ¼ 0.993). Moreover, consistent with previous studies, 31,32 our study demonstrated that pathological tumor size is a significant risk factor in both the solid and part-solid groups.…”
Section: Discussionsupporting
confidence: 60%
“…As for age, there seem to be controversies in previous studies, with some researchers believing that old age is associated with worse survival 27,28 and others not believing this. 29,30 In our study, we also found that old age was associated with worse survival in only the solid group (p ¼ 0.030) and not in the part-solid group (p ¼ 0.993). Moreover, consistent with previous studies, 31,32 our study demonstrated that pathological tumor size is a significant risk factor in both the solid and part-solid groups.…”
Section: Discussionsupporting
confidence: 60%
“…Approximately 75% of patients are diagnosed with metastatic or advanced cancer and often lose the opportunity for radical surgery. With the improvements of modern clinical diagnostic methods, the survival rate is still unsatisfactory, only ∼15%, although the overall survival rate and the quality of life have been improved (Siegel et al, 2015;Franceschini et al, 2017). In recent years, in addition to improving the treatment of lung cancer patients, searching for effective tumor markers to guide clinical diagnosis has become a hot spot in LUAD research.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant aspect reported by Franceschini et al 15 concerns mortality. No differences regarding mortality were found in the different age groups evaluated.…”
mentioning
confidence: 93%
“…In the present issue of JBP, Franceschini et al 15 provide relevant information on the epidemiology of patients with NSCLC in Brazil. In their retrospective cohort involving 790 patients from a tertiary center in the city of São Paulo, Brazil, who were followed between 2000 and 2012, the distribution of patients with NSCLC was heterogeneous: in younger patients (< 72 years of age) and in women, the predominant histological type was adenocarcinoma.…”
mentioning
confidence: 99%